Flora lenhosa do cerrado maranhense: diversidade, composição florística e modelagem com vistas a conservação - CAMPOS, Jamerson Rodrigo dos Prazeres (2023)
The Cerrado is considered the richest savanna in the world in terms of biodiversity, covering about 64% of the Maranhão territory, composed of a vegetational complex with ecotones and different phytophysiognomies. Besides being threatened by the opening of new agricultural frontiers, the Cerrado is still little known in the state, being listed among the priority areas for surveys of woody vegetation by the Ministry of Environment. The present work aimed to expand the knowledge of the woody flora of the Cerrado Maranhão state, in order to support conservation strategies for the biome. For this, an updated checklist of Cerrado species occurring in the territory of Maranhão was carried out, complemented with physical and virtual herbaria, as well as the use of tools "Kernel Density" and multicriteria analysis to present the highest priority areas for botanical collections. A total of 790 species were listed, 13 of which were classified as endangered, distributed among 302 genera and 79 families. The species Erythroxylum timothei Loiola & M.F. Sales, Moquilea maranhensis (Prance) Sothers & Prance and Ocotea barbellata Vattimo-Gil as exclusive records from Maranhão, it was also demonstrated that, in general, the areas towards the center to the south present a higher priority for new collections, due to the greater deficit of records and fewer protected areas. Subsequently, a phytosociological analysis of the woody stratum of an area of Cerrado sensu stricto in São João do Paraíso, Maranhão, was carried out, in which the structural analysis highlighted Emmotum nitens (Benth.) Miers, Tachigali vulgaris L.G.Silva & H.C.Lima, Vochysia gardneri Warm., Qualea grandiflora Mart., Parkia pendula (Willd.) Benth. ex Walp. e Caryocar brasiliense Cambess. as predominant species in the area, due to the highest value of importance, presenting diversity indices of Shannon and Pielou's equability above average for the Cerrado of Maranhão. Finally, the predictive modeling of the endangered species Peltogyne maranhensis Huber ex Ducke was carried out, based on the geographic information of this species found in floristic inventories and with secondary data from online herbaria associating them with environmental variables, using the Biodynamics software. The species has few known records of occurrence, the environmental variables of greatest influence on the distribution model were the soil, vegetation and temperature, and the northwestern, central and southwestern regions of Maranhão showed greater environmental suitability for the establishment of Peltogyne maranhensis, indicating possible ecological niche of the species. Predictive modeling of the geographic distribution of species can be an important tool to guide new scientific research aimed at the conservation and management of species, especially rare and endangered species.